PEMBUATAN HANDOUT MULTIMEDIA INTERAKTIF DENGAN MENGGUNAKAN APLIKASI COURSE LAB BERBASIS PENDEKATAN SAINTIFIK PADA PEMBELAJARAN FISIKA KELAS X SMA - Yulia Pratiwi; Festiyed Festiyed; Djusmaini Djusmaini (Universitas Negeri Padang, 2017)
Instructional media used by educators in the learning process of physics have not been optimal in motivating students to be active and independent in learning. In addition, there are many schools that do not have teaching materials in accordance with the demands of the curriculum in 2013 that emphasizes the scientific approach, teaching materials in schools is still limited to print teaching materials and interactive yet. The solution of this problem through interactive multimedia handout that has been designed. This study aims to produce interactive multimedia handout by using application-based lab course scientific approach to learning physics class X SMA valid and practical. This research is the development (research and development) using a model of R & D Sugiyono. This model consists of 10 stages, but this study only to the seventh stage, include: to recognize the potential and problems, gather information, product design, validate designs, revised the design, test new products, and revise product. Subjects were 3 people validator, 2 educators, and students in one class X SMA 15 Padang to practicalities. Data were analyzed with descriptive analysis techniques. Based on research that has been done, the resulting product in the form of interactive multimedia handout. Product research is at a very valid criteria for the validation of aspects of content, presentation, kegrafikan, and language with an average value of 90.93%. Product research is at a very practical criterion by educators from the aspects of ease of use, efficiency of learning time, and benefit with an average value of 94.5%. Product research is also on a very practical criterion by learners with an average value of 83.2% from the aspects of ease of use of navigation, ease of use guidelines, the use of multimedia, and the motivation of learners